Indigenous food harvesting as social-ecological monitoring: A case study with the Gitga'at First Nation - Thompson, Kim-Ly; Hill, Cameron; Ojeda Villarroel, Jaime Andrés; Ban, Natalie C.; Picard, Chris R. (My University, 2020)
1. Indigenous peoples have been monitoring and managing the natural resources in their homelands and waters for millennia. Meanwhile, social-ecological systems thinkers are embracing the capacity of Indigenous knowledge systems, which are informed by land-based practices, to inform adaptive management. 2. Following the collaborative design of a community-based social-ecological monitoring system over two traditional seafood harvesting seasons, we conducted a conceptual framework analysis of meeting notes and interview transcripts with Gitga'at harvesters and knowledge holders to discern how Gitga'at people monitor their territory and what indicators they focus on. 3. An interconnected set of social-ecological concepts and indicators emerged, evidencing an intrinsic part of Gitga'at life: Gitga'at harvesters closely monitor their coastal social-ecological system through ongoing land- and sea-based practices. 4. The conceptual framework highlights the importance of maintaining and revitalizing Indigenous knowledge and harvesting practices to inform social-ecological monitoring and adaptive management at local and broader scales. 5. Amidst discussions of marine and coastal resource co-management in British Columbia, our results also suggest opportunities for scientific approaches to situate themselves within and support existing Indigenous frameworks and priorities. 6. This research also adds to the discussion on the development of appropriate regional and global indicators and frameworks to monitor the resilience of social-ecological systems.
Keywords: biocultural indicators; community-based monitoring; conceptual framework; environmental monitoring; indigenous food systems; indigenous knowledge; land-based practices; participatory research; reciprocity; relational values